Design and Manufacturing of Organic Waste Chopping Machines - Endang Prihastuty; Bobby Saputra; W. Djoko Yudisworo (Mestro, 2021)
This research was conducted to find a solution to the problem of waste, especially organic waste which is generated from households and shopping centers, especially traditional markets. Many people do not understand how to deal with waste properly. The most common way that most people do is by burning organic waste. This has a negative impact on the environment and public health itself. Therefore it is necessary to do research on how this organic waste can be utilized for the benefit of society. One way to overcome the problem of organic waste is to make an organic waste chopper. The machine is equipped with a knife designed in such a way that it is capable of cutting to small sizes. In this study, this organic waste chopping machine will be used to produce pieces of waste which will then be used as biogas reactor material. To be continued in the process of making biogas. From the research results obtained the following machine specifications: Machine size with a length of 0.704 m, a width of 0.413 , and a height of 0.601 m. This organic waste shredder uses a motor with a power of 5.5 hp, a belt length of 798.47 mm, a drive pulley rotation of 2784.65 rpm and a blade rotation speed of 7.35 m/s.